Low molecular weight heparin suppresses receptor for advanced glycation end products‐mediated expression of malignant phenotype in human fibrosarcoma cells. Issue 6 (24th March 2013) - Takeuchi, Akihiko; Yamamoto, Yasuhiko; Munesue, Seiichi; Harashima, Ai; Watanabe, Takuo; Yonekura, Hideto; Yamamoto, Hiroshi; Tsuchiya, Hiroyuki
<x xml:space="preserve">Abstract</x> The receptor for advanced glycation end products (RAGE) is a pattern‐recognition receptor and its engagement by ligands such as high mobility group box 1 (HMGB1) is implicated in tumor growth and metastasis. Low molecular weight heparin (LMWH) has an antagonistic effect on the RAGE axis and is also reported to exert an antitumor effect beyond the known activity of anticoagulation. However, the link between the anti‐RAGE and antitumor activities of LMWH has not yet to be fully elucidated. In this study, we investigated whether LMWH could inhibit tumor cell proliferation, invasion, and metastasis by blocking the RAGE axis using in vitro and in vivo assay systems. Stably transformed HT1080 human fibrosarcoma cell lines were obtained, including human full‐length RAGE‐overexpressing (HT1080RAGE), RAGE dominant‐negative, intracellular tail‐deleted RAGE‐overexpressing (HT1080dnRAGE), and mock‐transfected control (HT1080mock) cells. Confocal microscopy showed the expression of HMGB1 and RAGE in HT1080 cells. The LMWH significantly inhibited HMGB1‐induced NFκB activation through RAGE using an NFκB‐dependent luciferase reporter assay and the HT1080 cell lines. Overexpression of RAGE significantly accelerated, but dnRAGE expression attenuated HT1080 cell proliferation and invasion in vitro, along with similar effects on local tumor mass growth and lung metastasis in vivo. Treatment with LMWH significantly inhibited the migration, invasion, tumor formation, and lung metastasis of HT1080RAGE cells, but not of HT1080mock or HT1080dnRAGE cells. In conclusion, this study revealed that RAGE exacerbated the malignant phenotype of human fibrosarcoma cells, and that this exacerbation could be ameliorated by LMWH. It is suggested that LMWH has therapeutic potential in patients with certain types of malignant tumors.